Private L.A. : Private #6 - Patterson, James, 1947-; Sullivan, Mark T.; Green, Dan, 1975-; Snyder, Jay (New York : Hachette Audio, 2014)
When Hollywood's biggest superstar couple disappears without a word from their ranch, private investigator Jack Morgan confronts dangerous secrets to expose an underworld of desperation and deception.
Title from container.
Read by Jay Snyder.
Keywords: Private investigators -- Fiction; Private security services -- Fiction; Los Angeles (Calif.) -- Fiction; Mystery fiction; Suspense fiction; Audiobooks